Efficacy and safety of one-month DAPT followed by 23-month ticagrelor monotherapy in patients undergoing proximal LAD stenting: Insights from the GLOBAL LEADERS trial. (1st December 2020) - Takahashi, Kuniaki; Wang, Rutao; Kawashima, Hideyuki; Tomaniak, Mariusz; Gao, Chao; Ono, Masafumi; Hara, Hironori; Wykrzykowska, Joanna J.; de Winter, Robbert J.; Werner, Nikos; Teiger, Emmanuel; Almeida, Manuel; et al.
Abstract: Backgrounds: Data on optimal antiplatelet therapy in patients undergoing stenting of the proximal left anterior descending artery (LAD) are limited. Methods: This is a post-hoc analysis of the GLOBAL LEADERS trial, a prospective, multi-center, randomized controlled trial, comparing the experimental strategy (1-month dual anti-platelet therapy [DAPT] followed by 23-month ticagrelor monotherapy) with the reference regimen (12-month DAPT followed by 12-month aspirin monotherapy) in relation to stenting of the proximal LAD. The primary endpoint was the composite of all-cause death or new Q-wave myocardial infarction (MI) and key secondary safety endpoint was Bleeding Academic Research Consortium (BARC) type 3 or 5 bleeding at two years. Results: Among 15, 845 patients included in the analysis, 3823 (23.9%) patients underwent stenting of the proximal LAD, while 12, 022 (75.2%) did not. In the proximal LAD stenting group, there was no significant difference in the risk of the primary endpoint between the two antiplatelet strategies (3.38% vs. 3.93%; hazard ratio [HR]:0.86; 95% CI:0.62–1.20; Pinteraction = 0.951). However, the risk of any MI (2.63% vs. 3.88%; HR:0.68; 95% CI:0.47–0.97; Pinteraction = 0.015) and any revascularization (7.84% vs. 9.94%; HR:0.78; 95% CI:0.63–0.97; Pinteraction = 0.058) was significantly lower in the experimental strategy group, while demonstrating a similar risk of BARC type 3 or 5 bleeding between the two antiplatelet strategies (1.93% vs. 1.99%; HR:0.98; 95% CI:0.62–1.54; Pinteraction = 0.981). Conclusions: The present study showed patients having stenting to the proximal LAD could potentially benefit from the experimental strategy with lower ischaemic events without a trade-off in major bleeding at two years. Highlights: The proximal LAD segment has been considered at a higher risk for adverse events. Few studies have evaluated optimal antiplatelet regimens in this specific cohort. Ticagrelor monotherapy reduced ischemic risks in patients with stenting to proximal LAD. These favourable benefits were achieved without an increased risk of major bleeding.